CASTAway: An asteroid main belt tour and survey. Issue 8 (15th October 2018) - Bowles, N.E.; Snodgrass, C.; Gibbings, A.; Sanchez, J.P.; Arnold, J.A.; Eccleston, P.; Andert, T.; Probst, A.; Naletto, G.; Vandaele, A.C.; de Leon, J.; Nathues, A.; et al.
Abstract: CASTAway is a mission concept to explore our Solar System's main asteroid belt. Asteroids and comets provide a window into the formation and evolution of our Solar System and the composition of these objects can be inferred from space-based remote sensing using spectroscopic techniques. Variations in composition across the asteroid populations provide a tracer for the dynamical evolution of the Solar System. The mission combines a long-range (point source) telescopic survey of over 10, 000 objects, targeted close encounters with 10–20 asteroids and serendipitous searches to constrain the distribution of smaller (e.g. 10 m) size objects into a single concept. With a carefully targeted trajectory that loops through the asteroid belt, CASTAway would provide a comprehensive survey of the main belt at multiple scales. The scientific payload comprises a 50 cm diameter telescope that includes an integrated low-resolution ( R = 30–100) spectrometer and visible context imager, a thermal (e.g. 6–16 µm) imager for use during the flybys, and modified star tracker cameras to detect small (∼10 m) asteroids. The CASTAway spacecraft and payload have high levels of technology readiness and are designed to fit within the programmatic and cost caps for a European Space Agency medium class mission, while delivering a significant increase in knowledge of our Solar System.